Intravesical bacillus Calmette-Guerin (BCG) in treating non-muscle invasive bladder cancer—analysis of adverse effects and effectiveness of two strains of BCG (Danish 1331 and Moscow-I) - Yuvaraja B. Thyavihally; Preetham Dev; Santosh Waigankar; Abhinav Pednekar; Nevitha Athikari; Abhijit Raut; Archan Khandekar; Naresh Badlani; Ashishkumar Asari (Asian Journal of Urology, 2022)
Objective: To compare the differences in adverse effects and efficacy profile between bacillus Calmette-Guerin (BCG) Danish 1331 and BCG Moscow-I strain in management of non-muscle invasive bladder cancer. Methods: Clinical data of 188 cases of non-muscle invasive bladder cancer treated with BCG between January 2008 and December 2018 in our institute were collected prospectively and analysed retrospectively, and 114 patients who completed a minimum of 12 months of follow-up were analysed. Patient and tumor characteristics, strain of BCG, adverse effects, and tumor progression were included for analysis. Intravesical BCG was instilled in intermediate- and high-risk patients. Six weeks of induction BCG, followed by three weekly maintenance BCG at 3, 6, 12, 18, and 24 months was advised in high-risk patients. Results: Overall 68 patients received BCG Danish 1331 strain and 46 patients received Moscow-I strain. Patient and tumor characteristics were well balanced between the two groups. The median follow-up period was 42.5 months and 34.5 months in Danish 1331 and Moscow-I groups, respectively. Adverse events like dropout rate, antitubercular treatment requirement, and need of cystectomy were higher in Moscow-I group (n=31, 67.4%) when compared to Danish 1331 strain (n=33, 48.5%) (p=0.046). On direct comparison between Danish 1331 and Moscow-I strain, there was similar 3-year recurrence-free survival (80.0% vs. 72.9%) and 3-year progression-free survival (96.5% vs. 97.8%). Conclusion: Study results suggest no significant differences between Danish 1331 and Moscow-I strain in recurrence-free survival and progression-free survival, but a significantly higher incidence of moderate to severe adverse events in BCG Moscow-I strain.